The role of apoptosis polymorphisms in individual susceptibility to Philadelphia-negative myeloproliferative neoplasms - Azevedo, Ana Paula (2015)
Poster presented at the 18th Annual Reunion of Sociedade Portuguesa de Genética Humana. Lisboa, 2014.